Nose-to-brain drug delivery: a short review of the available systems and their applications - Al-Hasnawi, Dhuha; Al-Azzawi, Shafq (Pharmakeftiki, 2025)
The brain is a crucial organ that controls most bodily functions; however, its protection by the blood-brain barrier (BBB) makes drug delivery to the brain difficult. The BBB prevents most drugs from entering the brain, which is a challenge for treating neurological diseases such as Parkinson disease, Alzheimer disease, multiple sclerosis, and stroke. The nasal-to-brain delivery route is a promising, non-invasive method to bypass the BBB, offering a direct connection between the nasal cavity and the central nervous system. This short review is focusing on ways through which drugs can reach the brain via the olfactory nerve, and the strategies to improve drug delivery through the intranasal route. In addition, it discusses the advantages and limitations of this type of drug administration and the recent formulations and applications of intranasal drug delivery with examples. Intranasal drug delivery holds great promise for treating neurological diseases and other conditions such as pain and cancer, and also provides a mean for reusing drugs that otherwise fail to reach the brain through the BBB. However, further developments in terms of the used formulations and the overcoming of challenges relating to absorption and mucosal irritation are essential for its widespread use in clinical settings.